Increase of cetaceans` ship strikes in the Canary Islands - Arbelo Hernández, Manuel Antonio; Sierra Pulpillo, Eva María; Bernaldo de Quirós Miranda, Yara; Carrillo Carrillo, Manuel; Tejedor, Marisa; De La Fuente Marquez, Jesus; Suarez Santana, Cristian Manuel; Arregui Gil, Marina; Puig Lozano, Raquel Patricia; Câmara , Nakita; Felipe Jiménez, Idaira; Consoli, Francesco; et al. (2019)
The Canary Islands is an archipelago composed of seven main volcanic islands, located in the northwest of Africa. It is one of the richest areas for cetacean biodiversity in the Northeast Atlantic, with 30 species identified. Strikes between vessels and cetaceans have become an issue of concern in the last decades due to an increase of the number and speed of ships. Areas with high cetacean diversity and high maritime traffic overlap have been identified as hot spots as ship strikes may compromise the population status of some cetacean species in those areas. In Europe, these areas include the Ligurian Sea, the Helenic Trench and the Balearic Islands in the Mediterranean Sea, the Strait of Gibraltar, and the Canary Islands. International but mainly inter-island ferry traffic in the Canarian waters has increased considerably in the last years including normal ferries, fast ferries, and high-speed ferries. According to the Canary Islands Cetacean Stranding Network data, ship collisions have affected a total of 81 cetaceans belonging to 12 species in the last 20 years (7 misticetes and 74 odontocetes: 5 short finned pilot whales, 10 pigmy sperm whales, 11 beaked whales, 46 sperm whales and 2 small delphinids), 33 of these cases were confirmed by forensic studies. The average per year of ship strikes in this period (1999-2018) is 4.5, 0.37 per month. During the months of January to April of 2019, 4 confirmed cases affecting to sperm whales (3) and Bryde´s whale (1), and another possible case, affecting a short-finned pilot whale, have been reported. This increase in ship strikes (from 0.37 to at least 1 per month) in the Canary Islands is coincidental in time with the introduction of new high-speed ferry routes, raising the concern of the impact of ship strikes in the conservation of sperm whales.